2009
DOI: 10.1093/jpepsy/jsp006
|View full text |Cite
|
Sign up to set email alerts
|

Parental HIV/AIDS and Psychosocial Adjustment among Rural Chinese Children

Abstract: The findings underscore the urgency and importance of culturally and developmentally appropriate intervention efforts targeting psychosocial problems among children affected by AIDS and call for more exploration of risk and resilience factors, both individual and contextual, affecting the psychosocial wellbeing of these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 14 publications
2
71
0
Order By: Relevance
“…37 Psychosocial problems of these children call for exploration of risk and resilience factors. 20 Communication about the illness or death of loved ones is an important step for recovery from grief. 38 Open communication with others can provide affected children opportunities of receiving emotional support and coping strategies, therefore, their needs and problems could be heard and addressed appropriately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Psychosocial problems of these children call for exploration of risk and resilience factors. 20 Communication about the illness or death of loved ones is an important step for recovery from grief. 38 Open communication with others can provide affected children opportunities of receiving emotional support and coping strategies, therefore, their needs and problems could be heard and addressed appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Henan, is an agricultural province in central China with a population of 96.7 million. 20 It was estimated that at least 100,000 AIDS orphans lived in China by the end of 2004, and many of identified AIDS orphans live in rural Henan. 21 It is important to understand the situation of these children and their families in rural area, who have not yet attracted as much attention as the ones in China's developed areas.…”
mentioning
confidence: 99%
“…We anticipated that the SACAA score would be positively associated with other measures of HIV stigma and psychopathology symptoms (e.g., depression, loneliness) and negatively associated with psychosocial well-being (e.g., self-esteem, positive future orientation, hopefulness, perceived control over the future). Because previous research [31] suggested a strong association of psychosocial adjustment with children's orphanhood status, sex, age and their family SES, the bivariate associations between SACAA and psychosocial adjustment were further verified using General Linear Model (GLM) analysis controlling for orphanhood status, sex, age, and family SES. To use SACAA score as a between-subjects factor in GLM, a categorical score of SACAA was created by dividing the participants into three groups based on children's scores on the SACAA (i.e., approximately bottom 25%, middle 50%, and top 25%).…”
Section: Discussionmentioning
confidence: 99%
“…Age eligibility was verified through local community leaders, school records, or caregivers. Both the recruitment process and consenting procedure for the current study have been described in detail elsewhere [31]. Briefly, the orphanage sample was recruited from four governmentfunded orphanages (n = 176) and eight community-based small group homes (n = 30).…”
Section: Participants and Samplingmentioning
confidence: 99%
“…Delva and colleagues also confirmed the sparse social network of friends and low social support from the family for AIDS orphans in Guinea [5]. Social support is located within local cultural and social contexts, and is often impacted by education, church activities, extended family and community members [21,[32][33][34]. Children who receive adequate support from family, peers and others adapt well psychosocially while those who do not become depressed, lonely and withdrawn [35].…”
Section: Introductionmentioning
confidence: 99%